Odpowiedzi

Najlepsza Odpowiedź!
2009-12-07T21:49:54+01:00
A) (x+1)(x+2)(x+3)=
= (x²+2x+x+2)(x+3)=
=x³+3x³+2x²+6x+3x+x²+2x+6=
4x³+3x²+12x+6

b) (x-2)(x+5)(2x-1)=
= (x²+5x-2x-10(2x-1)=
= 2x³-x²+10x²-5x-4x²+2x-20x+10=
= 2x³+5x²-23x+10

c)(x-4)(x+1)²=
(x-4)(x²+1+2x)=
=x³+x+2x²-4x²-4-8x=
=x³-2x²7x-4

d)(2x-3)²(x+2)=
=(4x²+9-12x)(x+2)=
= 4x³+9x-12x²+8x²+18-24x=
= 4x³-4x²-15x+18

Mam nadzieje ze się gdzieś nie machnęłam :):):)
1 5 1
2009-12-07T21:54:28+01:00
Zad. Zapisz w postaci sumy algebraicznej:

a) (x+1)(x+2)(x+3)= (x²+2x+x+2)(x+3)=(x²+3x+2)(x+3)=
=x³+3x²+3x²+9x+2x+6=x³+6x²+11x+6
c)(x-4)(x+1)²=(x-4)(x²+2x+1)=x³+2x²+x-4x²-8x-4=x³-2x²-7x-4
b) (x-2)(x+5)(2x-1)=(x²+5x-2x-10)(2x-1)=(x²+3x-10)(2x-1)=
=2x³-x²+6x²-3x-20x+10=2x³+5x²-23x+10
d) (2x-3)²(x+2)=(4x²-12x+9)(x+2)=4x³+8x²-12x²-24x+9x+18=
=4x³-4x²-15x+18